2015
DOI: 10.1111/ger.12217
|View full text |Cite
|
Sign up to set email alerts
|

Sedative load, carious teeth and infection in the periodontium among community‐dwelling older people

Abstract: Presence of dental caries was associated with the use of drugs with sedative properties. The use of drugs with sedative properties was not associated with the presence of periodontal pockets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The study protocol was approved by the ethics committee of Kuopio University Hospital and the University of Kuopio. Further information about the GeMS study can be found from previous studies …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study protocol was approved by the ethics committee of Kuopio University Hospital and the University of Kuopio. Further information about the GeMS study can be found from previous studies …”
Section: Methodsmentioning
confidence: 99%
“…Further information about the GeMS study can be found from previous studies. [16][17][18] A multidisciplinary team (two nurses, two physiotherapists and two physicians) carried out the comprehensive geriatric assessment, which included interviews and clinical examinations. In situations where the participant could not answer the questions because of his/ her cognitive or other impairment, a close relative or a caregiver provided the answers.…”
Section: Our Study Population Is Part Of a Larger Oral Health Geriatricmentioning
confidence: 99%
“…Apart from the effects on physical and cognitive function, anticholinergic medication use has recently been demonstrated to affect other disease states. Secondary analysis of data collected for a large cross‐sectional study in Finland suggested that use of anticholinergic and sedative medications may increase risk of dental caries in older people . Another study analysed the data from several large randomised controlled trials and reported that inhaled anticholinergic medications, such as ipratropium and tiotropium, have the potential to increase the risk of serious cardiovascular events, including mortality, when used in the treatment of chronic obstructive pulmonary disease.…”
Section: Anticholinergic Adverse Events In Older Adultsmentioning
confidence: 99%